Bio-based polymers for sustainable packaging and biobarriers: A critical review - Karoliina Helanto; Lauri Matikainen; Riku Talja; Orlando J. Rojas (BioResources)
Barrier materials have an important role in various packaging applications, especially considering the requirements associated with protection and shelf life. Most barrier materials used in today’s industry are either manufactured from oil resources or metals. Driven by the increase in environmental awareness, access to oil resources as well as legislation, new and environmentally benign alternatives are at the center stage of scientific and industrial interest. This article covers the use of wood-derived polymers and those produced from microorganisms, which display remarkable barrier properties. Wood-based products have received great attention for their air/oxygen resistance. As far as their properties, microorganism-derived biopolymers are comparable to conventional oil-based thermoplastics, but their cost may still be an issue. Both, wood and microorganism-derived biopolymers are challenged when moisture, grease and oxygen resistance are simultaneously required. Hence, multilayer structures and composites are needed to fulfill the most demanding requirements of packaging materials. Here we offer a review of these topics together with a discussion of their prospects.